Linear approximation of bilinear Processes - Ai Hui , Tan (2005)
The linear approximation for a first-order bilinear process perturbed using pseudorandom binary and ternary signals is studied, in terms of the related linear dynamics consisting of the underlying linear dynamics and bias caused by nonlinear distortions. The related time constant is derived from the input-output cross-correlation function. The analysis is extended by simulation to the case of multilevel input signals. Simulation results are also given for a second-order bilinear process, as theoretical results are not available.